Physical Medicine & Rehabilitation Two-Volume Ses - Joel A. Delisa, Gans, Bruce M.; Walsh, Nicolas E.; Bockenek, William L.; Frontera, Walter R.; Geiringer, Steve R.; G (Lippincott Williams & Wilkins, 2005)

(untitled)
Physical Medicine and Rehabilitation focuses on the restoration of function and reintegration into the community. These volumes are organized to assist the practitioner in these endeavors. This two-volume edition does not imply a division of physical medicine and rehabilitation medicine; this format was selected for ease of use by the practitioner and to accommodate the ever-increasing knowledge in the field of physical medicine and rehabilitation. In response to the many advances in the field of physiatry, this textbook contains 88 chapters. Our goal was to provide comprehensive and multidisciplinary coverage of the depth and breadth of the field of physical medicine and rehabilitation, both in basic principles and in practical techniques of patient management. Each chapter was a collaborative effort by authors chosen for their expertise in the given topic area. This text reflects the efforts of over 223 contributing authors from all over the globe. The editors express their appreciation to each of the authors who have contributed to this edition. Their hard work and dedication have made this an exciting and productive effort. As an essential resource for the training of medical rehabilitation professionals, this text will help ensure that the care they provide to people with disabilities is of the highest quality, encompassing improvement in their health, function and quality of life. This fourth edition of Physical Medicine and Rehabilitation is dedicated to our colleagues of the past, present and future. Their passing is a loss of friendship, intellect and compassion to the field of physical medicine and rehabilitation. To ameliorate the void, we must challenge ourselves, and those around us, by our daily example, mentoring and care.